Molecular characterization of the first human G15 rotavirus strain of zoonotic origin from the bovine species. (13th April 2021) - Tsugawa, Takeshi; Fujii, Yoshiki; Akane, Yusuke; Honjo, Saho; Kondo, Kenji; Nihira, Hiroshi; Kimura, Hirokazu; Kawasaki, Yukihiko
Abstract : Group A rotaviruses (RVAs) infect a wide variety of mammalian and avian species. Animals act as a potential reservoir to RVA human infections by direct virion transmission or by contributing genes to reassortants. Here, we report the molecular characterization of a rare human RVA strain Ni17-46 with a genotype G15P[14], isolated in Japan in 2017 during rotavirus surveillance in a paediatric outpatient clinic. The genome constellation of this strain was G15-P[14]-I2-R2-C2-M2-A13-N2-T9-E2-H3. This is the first report of an RVA with G15 genotype in humans, and sequencing and phylogenetic analysis results suggest that human infection with this strain has zoonotic origin from the bovine species. Given the fact that this strain was isolated from a patient with gastroenteritis and dehydration symptoms, we must take into account the virulence of this strain in humans.